(untitled) (Research, Society and Development, 2022)
Aim: to know the suffering when falling ill during the care of black women living with breast cancer attended at a reference center in the state of Bahia. Methodology: Qualitative research conducted in a reference service with the participation of 12 women who were interviewed chosen by data saturation and had content analysis as a technique of data interpretation. Results: Structural racism is a condition that contributes intensely to the suffering during the illness of black women with breast cancer, since their life histories are marked by prejudice and discrimination, which exacerbate with this disease when associated with elements of whiteness, social inequalities and existing barriers to access. Care should have strengthened in its action with tools such as listening, dialogue, welcoming and the production of bonds, with strategies to recognize the intersubjective relationships existing in the worker-user relationship. However, economic vulnerability appears as an element that contributes unsatisfactory to the failure of care of these women, in which it widens the gap between black and white that it sometimes uses from the private sector to solve their health problems. Conclusion: black women have a life of suffering due to the epidemic tone due to the intersectionality of patriarchy, structural racism and social inequality, when diagnosed with breast cancer and in the face of immanent stigmas, suffering widens by the consequences of the disease, and are maximized by the difficulties faced in trying to solve their needs.